DEVELOPMENT TRENDS OF THE RURAL TOURISM INDUSTRY IN THE REPUBLIC OF MOLDOVA - Chistol, Andrei; Bulat, Veronica (CEP USM, 2022)
The national tourism development policy is geared towards promoting the country's image, aimed at generating domestic, regional and international tourism demand. The Republic of Moldova, as a tourist destination, is little known abroad, compared to the destinations of neighboring countries, yet the central and non-governmental authorities are constantly engaged in developing and strengthening the regulatory and promotional framework of standardized information packages, which would make the image of our country more attractive. Following the social, political and regional conjuncture, the development of rural tourism is a niche that can be efficiently developed in the context of the development of the tourism industry in the Republic of Moldova.
Keywords: sustainable development; rural tourism; development policy; investment project